PENGARUH PERKUATAN GESER FIBER REINFORCED POLYMER TERHADAP BEBAN DAN LENDUTAN BALOK BETON - Jabair, Jabair; Idris, Muhammad; Djamal, Aksan (FORUM BANGUNAN, 2013)
Fiber Reinforced Polymer ( FRP ) is a material that is lightweight, strong, antimagnetic and corrosion resistant. This material can be used as an option to replace steel as reinforcement material in the construction of reinforced concrete or as material to add strength to existing construction. This study aims to determine: the behavior of the influence shear strengthening fiber reinforced polymer toward load and deflection concrete beam in the structure by the method of FRP reinforcements on the outer side of a sheet of woven carbon fiber. The shape and spacing of windings, namely: winding method U with the distance of each winding 50 mm and 150 mm . This study begins with a tensile steel ( fy ), the test characteristics of aggregate , concrete mix design f'c = 25Mpa, making concrete cylinders Ã˜ = 15 c, t = 30cm, curing and compressive strength test 28 days. Furthermore, to analysis beam, sheets of woven carbon fiber. Then given the test object beam shear reinforcement in the form of woven carbon fiber sheets by the method of winding U with the distance of each winding 50 mm and 150 mm. Shear strength capacity test is done with concrete beam flexural test. The maximum load for the results of this study of normal concrete beams, FRP U-50mm, U150mm respectively were: 67 kN, 70KN, 70KN and deflection were: 1.94 mm, 2.94 mm and 2.79 mm. Key words : Load, deflection, shear, FRP